2015
DOI: 10.1016/j.ajhg.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Mouse and Human CRKL Is Dosage Sensitive for Cardiac Outflow Tract Formation

Abstract: The human chromosome 22q11.2 region is susceptible to rearrangements during meiosis leading to velo-cardio-facial/DiGeorge/22q11.2 deletion syndrome (22q11DS) characterized by conotruncal heart defects (CTDs) and other congenital anomalies. The majority of individuals have a 3 Mb deletion whose proximal region contains the presumed disease-associated gene TBX1 (T-box 1). Although a small subset have proximal nested deletions including TBX1, individuals with distal deletions that exclude TBX1 have also been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…More generally, our observations support the idea that a single primary genetic lesion can result in a range of OFT defects, which in clinical practice are often considered discrete entities (Dorfman and Geva, 2006;Johnson, 2010). Our data also support the idea that complex alignment phenotypes might form a continuous spectrum of related OFT alignment disorders, as others have also proposed based on observations from other mouse genetic models, particularly for Tbx1 and related pathways (Brown et al, 2004;Racedo et al, 2015;Rana et al, 2014;Vincentz et al, 2005).…”
Section: Results and Discussion Mef2c Is Required For Proper Oft Aligsupporting
confidence: 77%
“…More generally, our observations support the idea that a single primary genetic lesion can result in a range of OFT defects, which in clinical practice are often considered discrete entities (Dorfman and Geva, 2006;Johnson, 2010). Our data also support the idea that complex alignment phenotypes might form a continuous spectrum of related OFT alignment disorders, as others have also proposed based on observations from other mouse genetic models, particularly for Tbx1 and related pathways (Brown et al, 2004;Racedo et al, 2015;Rana et al, 2014;Vincentz et al, 2005).…”
Section: Results and Discussion Mef2c Is Required For Proper Oft Aligsupporting
confidence: 77%
“…Zhao et al [2013] reported on a cohort specifically with cardiac defects, and identified a single individual with a central deletion, but the types of cardiac defects are not specified. In Racedo et al [2015], 8/20 B-D deletion subjects and 1/5 C-D deletion subjects had cardiac defects. These included conotruncal defects in 4/25, TOF in 3/25, interrupted aortic arch in 1/25, VSD in 4/25, and atrial septal defect (ASD) in 2/25.…”
Section: Central Deletions (B-d C-d)mentioning
confidence: 99%
“…Of those, sufficient clinical information was provided for 23, resulting in a total of 68 individuals with clinical information ( table 1 ). The study by Racedo et al [2015] only examined cardiac features of 25 individuals with central deletion, so that total is only included in the cardiac category in table 1 , and those 25 are not included in the 45 reported individuals. Seven of the 31 individuals reported from our lab had follow-up studies performed, and 4 deletions were de novo, 2 were familial and 1 unknown.…”
Section: Central Deletions (B-d C-d)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the etiology underlying CTD requires elucidation. Previous studies have established the important role genetic risk factors serve in the pathogenesis of CTD (10)(11)(12)(13)(14)(15). The 22q11 deletion syndrome (22q11DS), also known as DiGeorge syndrome, is a chromosomal abnormality responsible for ~12% of conotruncal malformations (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%